Administrative removals and access to justice: between the penal state and social state / Remoções administrativas e acesso à justiça: entre o estado policial e o estado social - da Silva, Eliane Alves (Revista de Direito da Cidade, 2022)
Abstract The purpose of this study is to capture the status of administrative removals (removals that do not require a court order) as a way of managing urban illegality represented by low-income popular housing. For this purpose, it analizes the discourses of the public officials involved in the litigious created by local authorities decree-law issued by municipality of São Bernardo do Campo (SP) in 2017, with partial outcome in 2020 due to the unconstitutionality request sent to the Court of Justice of São Paulo by the Public Prosecutor. The request alleged that the decree violated constitutional rights such as affordable housing, access to justice, among others. The study interviewed agents from the local administration authorithies, State of São Paulo public defenders, and public prosecutors. Overall, this study showed that the use of administrative removals follows its own time and logic in conflict with the times and procedures of individual and social rights, disengaging the state and public policies from the register of social solidarity, and its minimum guarantees, to the register of a penal state. Keywords: access to justice; São Bernardo do Campo; urban removals; Law; poor housing